The Risk Factors of the Hip Dislocation After Total Hip Arthroplasty (Literature Review) - Zazirnyi, I.M.; Pinchuk, Ye.I. (TERRA ORTHOPAEDICA, 2022)
Summary. The dislocation of the endoprosthesis head is one of hip arthroplasty complications. In the vast majority of cases, the cause of dislocation is multifactorial. That is why only a thorough analysis of the patient’s peculiarities, surgery and rehabilitation will help to avoid the relapse. Risk factors associated with the patient include: old age, male gender, obesity, concomitant diseases, low level of preoperative physical activity, low compliance, and some others. The problem of biomechanical ratio in the segment “spine – pelvis – lower limb” deserves special attention. Besides, there are risk factors associated with the surgeon: access option, type of implant, fixation and position of endoprosthesis components, experience and surgical technique of the orthopedic surgeon. The strategy of dislocations rate reduction is based on a detailed study of dislocation causes and their elimination, and adequate surgery planning. The treatment of a patient with dislocation should take into account the multifactorial etiology of the condition.